2022
DOI: 10.1155/2022/5344508
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Exosomal MicroRNAs Derived from Cerebrospinal Fluid in Patients with Congenital Hydrocephalus Determined by MicroRNA Sequencing

Abstract: Purpose. Congenital hydrocephalus is one of the most common birth defects worldwide. Exosomal microRNAs (miRNAs) in body fluids have been implicated in many diseases. However, their involvement in cerebrospinal fluid from congenital hydrocephalus is not well understood. This study is aimed at investigating the role of dysregulated exosomal miRNAs in congenital hydrocephalus. Methods. We collected cerebrospinal fluid samples from 15 congenital hydrocephalus patients and 21 control subjects. We used miRNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Yoneda et al [ 28 ] identified hsa-miR-501-5p as a serum biomarker of chronic periodontitis. In addition, hsa-miR-501-5p, a significantly downregulated exosomal miRNA, has been detected in cerebrospinal fluid from congenital hydrocephalus patients [ 29 ]. No studies have reported the relationships of hsa_circ_0044724, hsa_circ_0137527, and hsa_circ_0117503 with diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yoneda et al [ 28 ] identified hsa-miR-501-5p as a serum biomarker of chronic periodontitis. In addition, hsa-miR-501-5p, a significantly downregulated exosomal miRNA, has been detected in cerebrospinal fluid from congenital hydrocephalus patients [ 29 ]. No studies have reported the relationships of hsa_circ_0044724, hsa_circ_0137527, and hsa_circ_0117503 with diseases.…”
Section: Discussionmentioning
confidence: 99%
“…With the sample size applied in the current findings, it is not yet reasonable to predict or utilize other mRNA markers as a diagnostic tool for AD (compared to control) given the number of other studies that have examined far larger cohort sizes ( Georganopoulou et al, 2005 ; Holtta et al, 2013 ). Although assaying mRNA in the blood ( Ekici et al, 2010 ) or CSF with NPH has been rarely reported, we found that an attempt has been made to detect microRNA in the CSF of patients with congenital hydrocephalus ( Chen et al, 2022 ). Nevertheless, we envision that the data presented in this report on a more specific marker gene like TRPV4 and MAPT in NPH can significantly improve the prior cases reporting misdiagnosis of either AD or NPH ( Joseph et al, 2006 ; Joseph et al, 2008 ; Lee et al, 2010 ; Shimada et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Orthogonal techniques to validate RNA‐seq and direct detection/hybridisation data can be used to promote reproducibility of results. For the 64 CSF EV studies that analysed RNA, eight articles (13%) used both RNA‐seq and qPCR (Chen et al., 2022; Hou et al., 2019; Lee et al., 2021; Otake et al., 2019; Prieto‐Fernández et al., 2019; Saugstad et al., 2017; Torii et al., 2022; Yagi et al., 2017), four (6%) used both direct digital detection/hybridisation arrays and qPCR (Feliciano et al., 2014; He et al., 2019; Kim et al., 2020; Wang et al., 2020), and one (2%) used both RNA‐seq and direct digital detection/hybridisation arrays (Tietje et al., 2014).…”
Section: Csf Ev Rna Studiesmentioning
confidence: 99%